Rising Arizona: Participation and Results of the 2018 Red for Ed Strike - Michelle Doughty (AERA Open)
In 2018, a wave of educator strikes called Red for Ed swept through several states. Educators in Arizona won additional funding from the state legislature, supposedly for teacher salaries, which school boards could spend as they chose. This article quantitatively examines the participation and results of the 2018 Arizona educator strike, using this example to speak to theoretical work on types of union activity. I find that after the strike, per-pupil funding, teacher salaries, and student support staff salaries all increased. However, poststrike funding was added to Arizona’s preexisting funding formula, which advantaged the small, rural, predominantly White districts whose educators were less likely to go on strike. Educators who went on strike (often from large, urban districts with low property wealth) thus received less money for their districts and smaller raises than nonparticipating educators. This raises important concerns about how free riders can affect different types of union organizing.